Pseudo-Landau levels splitting triggers quantum friction at folded graphene edge - Xinchen Gao; Zhenbin Gong; Hongli Li; Zhao Liu; Weishan Yan; Qingkai Zheng; Kexin Ren; Wenchao Wu; Junyan Zhang (Nature Communications)
Abstract From the construction of monumental pyramids to the manipulation of minuscule molecules, the utilization of friction has been inevitable, thereby driving rapid technological advancement. Concurrently, low-dimensional materials have transformed the concept of ultra-low friction into reality. Notably, materials with curved geometries-such as moiré patterns and nanotubes-consistently exhibit anomalous frictional phenomena that often contradict classical macroscopic friction laws. Here, we report a solid-solid interfacial quantum friction phenomenon, in which the friction at folded graphene edges increases nonlinearly with the number of layers, deviating from Amontons’ classical law, which is obeyed by exposed graphene edges. This anomaly is primarily attributed to the strain-induced pseudo-Landau quantized splitting, suppressing electronic energy dissipation at the folded graphene edge, while the phononic energy dissipates normally regardless of folding. This work establishes a bridge between the nanoscale curved geometries of low-dimensional materials and the mechanisms of frictional dissipation, thereby offering valuable insights for designing graphene dissipation-free topological quantum devices.